What Would Be the Best School Meal If You Were to Decide? Pupils’ Perceptions on What Constitutes a Good School Meal - Bruselius-Jensen, Maria (The International Journal of Sociology of Agriculture and Food, 2014)
Much attention is given to school meals as a way to prevent childhood obesity. This article is concerned with a perspective that is often lost in the present debate, namely the perspective of pupils on what constitutes a good meal. The article draws on the findings of an action research process in a Danish public school and presents the perspectives of a group of eighth-grade pupils, with the aim of voicing their opinions and positioning them as co-constructors of school meals. Inspired by the work of Henri Lefebvre and literature on the sociology of childhood and meals, the article demonstrates how pupils’ perspectives on what constitutes a good school meal are concerned with much more than food and are only associated weakly with healthy nutrition. Pupils perceive school meals as a means of being social and as a break from the order of school life. They are concerned with the construction of meal spaces and with the sensuous experience of eating. Subsequently, it is argued that there are both epistemological and ethical arguments for including pupils’ perspectives in research on school meals. Furthermore, including pupils’ preferences in the planning of school meals might eventually build school meals in which pupils enjoy to participate and are therefore more likely to be health promoting.